Are there social returns to both firm-level and regional human capital? Evidence from German social security data - Nils Braakmann (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2009)
This paper provides first evidence on the social returns to education from both firm-level and regional human capital. Using panel data from German social security, both at an individual and aggregated at the plant and regional level, I estimate earnings functions incorporating measures of regional and firm-level human capital while controlling for various types of unobserved heterogeneity, demand shocks, regional physical capital and other regional and firm-level confounders. The results suggest negligibly small external returns to the firm-level shares of high-skilled workers. On the regional level, the results show no support for external returns to education, except for skilled workers.
Keywords: D62; J24; J31; R11; 330; Human capital externalities; social returns to education; error-component model